Dose dependence of accelerated repopulation in head and neck cancer: Supporting evidence and clinical implications. Issue 1 (April 2018) - Shuryak, Igor; Hall, Eric J.; Brenner, David J.
Abstract: Background and purpose: Accelerated repopulation (AR) can compromise tumor control after conventional radiotherapy for fast-growing tumors. Standard AR models assume it begins at a fixed time, with repopulation rates independent of the number of clonogens killed. We investigate the validity and significance of an alternative model where onset-time and rate of AR depend on the number of clonogens killed, and thus on dose and dose-fractionation. Materials and methods: We analyzed tumor control (TCP) from randomized trials for head and neck cancer (HNC, 7283 patients), featuring wide ranges of doses, times, and fractionation-schemes. We used the linear-quadratic model with the standard dose-independent AR model, or with an alternative dose-dependent model, where AR onset and rate depend on clonogen killing. Results: The alternative dose-dependent model of AR provides significantly-improved descriptions of a wide range of randomized clinical data, relative to the standard dose-independent model. This preferred model predicts that, for currently-used HNC fractionation schemes, the last 5 fractions do not increase TCP, but simply compensate for increased accelerated repopulation. Conclusions: The preferred dose-dependent AR model predicts that, for standard fractionation schemes currently used to treat HNC, the final week (5 fractions) could be eliminated without compromising TCP, but resulting in significantly decreased late sequelae due to the lower overall dose.